2014
DOI: 10.1039/c4ta03431g
|View full text |Cite
|
Sign up to set email alerts
|

“Nano to nano” electrodeposition of WO3 crystalline nanoparticles for electrochromic coatings

Abstract: Nanoparticles in the dispersion are electrodeposited onto conductive substrates forming crystalline nano-structured films. The deposition process can be well manipulated, and the films prepared have excellent electrochromic performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 85 publications
(53 citation statements)
references
References 24 publications
4
49
0
Order By: Relevance
“…In the PEDOT:PSS film, the PEI layers may work as interlayer barrier for electron hopping between PEDOT:PSS layers [22], leading to inefficient charge transfer and hence lower coloration efficiency and slow switching speed than that of neat PEDOT:PSS films. However, in the WO 3 -NP film, the very rough surface created by randomly oriented disk-like WO 3 NPs and their interdigitated arrangement hinder the formation of a continuous PEI barrier layer between the WO 3 NPs, giving similar coloration efficiency as electrodeposited WO 3 -NP film [27]. Similarly, WO 3 NPs in the hybrid film may effectively interact with PEDOT:PSS, and the PEI layers cannot hinder the charge transfer between the electrochromic components.…”
Section: Electrochromic Properties Of the Filmsmentioning
confidence: 97%
See 1 more Smart Citation
“…In the PEDOT:PSS film, the PEI layers may work as interlayer barrier for electron hopping between PEDOT:PSS layers [22], leading to inefficient charge transfer and hence lower coloration efficiency and slow switching speed than that of neat PEDOT:PSS films. However, in the WO 3 -NP film, the very rough surface created by randomly oriented disk-like WO 3 NPs and their interdigitated arrangement hinder the formation of a continuous PEI barrier layer between the WO 3 NPs, giving similar coloration efficiency as electrodeposited WO 3 -NP film [27]. Similarly, WO 3 NPs in the hybrid film may effectively interact with PEDOT:PSS, and the PEI layers cannot hinder the charge transfer between the electrochromic components.…”
Section: Electrochromic Properties Of the Filmsmentioning
confidence: 97%
“…The WO 3 NPs were prepared via hyrdrothermal process from metallic W powder, which could be dispersed in water without any additives [26,27]. The electrochromic thin films were obtained by LBL self-assembly.…”
Section: Sample Preparationmentioning
confidence: 99%
“…Moreover, electrodeposition can be carried out at moderate potential, room temperature and in aqueous solutions. For example, we have shown that a variety of nanomaterials, such as latex nanoparticles [19], WO 3 nanorods [20], graphene [21] and carbon nanotubes [22] could be electrodeposited successfully following this approach. In most cases, the applied electrical potential caused the oxidation or reduction of water, which changed the pH on the electrode surface and eliminated the net surface charge of the dispersed nanomaterials causing them to aggregates and deposit irreversibly on the electrode surface.…”
Section: Introductionmentioning
confidence: 98%
“…Recently, we have demonstrated the direct deposition of nanomaterials from their dispersions using electrochemistry [19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…[11] Thehit-and-run phenomenon is the basis of emergent electrochemical devices,s uch as semi-solid flow batteries and electrochemical flow capacitors, [12] while the hitand-stay phenomenon offers the possibility of modifying electrode surfaces.L iu et al [13] made use of the hit-and-stay behavior to immobilize nanoparticles from asuspension onto at ransparent electrode for electrochromic applications.W e envisioned that the hit-and-stay phenomenon could be exploited to immobilize catalyst particles suspended in an electrolyte onto an electrode to form stable catalyst films with self-healing capability.T his concept can be exploited by adding catalyst particles into the electrolyte reservoir(s) of arunning electrolyzer (see Supporting Information, Figure S1 and S2). Nickel foil was chosen as the model current collector for both the cathode and anode because of the use of Ni-based electrodes in commercial alkaline water electrolyzers.…”
Section: à2mentioning
confidence: 99%